A rare cecal subepithelial tumor in a Crohn´s Disease patient - Silva, Joana Inês Alves da; Caetano, Cidalina; Rocha, Anabela Maria Sousa da; Lamas, Nuno Jorge; Lago, Paula; Pedroto, Isabel Maria Teixeira de Carvalho (Autopsy and Case Reports, 2021)
Appendiceal tumors comprise a variety of histologic types, including appendiceal mucinous neoplasms, which can be grouped as premalignant lesions, tumors of uncertain malignant potential, and malignant lesions. The appendiceal mucinous neoplasms are characterized by mucinous epithelial proliferation with extracellular mucin and pushing tumor margins, commonly an incidental finding during operative exploration. We report the case of a low-grade appendiceal mucinous neoplasm presenting as a subepithelial lesion in Crohn´s Disease patient. The diagnosis was not straightforward, and only surgical resection allowed an accurate diagnosis. Although Inflammatory Bowel Disease is a risk factor for the development of colorectal neoplasms, the absolute risk for appendiceal tumors is uncertain. The frequency of progression to malignancy remains to be determined.